Benefits of enhanced infection prophylaxis at antiretroviral therapy initiation by cryptococcal antigen status - Pett, SL; Spyer, M; Haddow, L; Nhema, R; Benjamin, L; Najjuka, G; Bilima, S; Daud, I; Musoro, G; Kitabalwa, J; Selemani, G; Kandie, S; et al. (Wolters Kluwer Health, 2020)
Objectives: To assess baseline prevalence of cryptococcal antigen (CrAg) positivity; and its contribution to reductions in all-cause mortality, deaths from cryptococcus and unknown causes, and new cryptococcal disease in the REALITY trial.